2011
DOI: 10.1113/jphysiol.2011.208447
|View full text |Cite
|
Sign up to set email alerts
|

The fusimotor and reafferent origin of the sense of force and weight

Abstract: Signals associated with the command the brain sends to muscles are thought to create the sensation of heaviness when we lift an object. Thus, as a muscle is weakened by fatigue or partial paralysis (neuromuscular blockade), the increase in the motor command needed to lift a weight is thought to explain the increasing subjective heaviness of the lifted object.With different fatiguing contractions we approximately halved the force output of the thumb flexor muscles, which were then used to lift an object. For tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 35 publications
(51 reference statements)
4
98
0
2
Order By: Relevance
“…Studies of fatigue and/or sensory reweighting have proposed that altered afferent signaling contributes to the perception of effort (Luu, Day, Cole, & Fitzpatrick, 2011) and contributes to associated altered motor patterns (Carpenter, Murnaghan, & Inglis, 2010;Eva-Maj, Hans, Per-Anders, & Mikael, 2013). The results of our study are consistent in showing that disturbances of the sensory system, quantified by increases in sensory thresholds (i.e., declines in afferent signaling of event detection), are related to, and possibly part of, mechanisms influential in generating greater changes in motor patterns.…”
Section: Association Between Motor and Sensory Changessupporting
confidence: 79%
“…Studies of fatigue and/or sensory reweighting have proposed that altered afferent signaling contributes to the perception of effort (Luu, Day, Cole, & Fitzpatrick, 2011) and contributes to associated altered motor patterns (Carpenter, Murnaghan, & Inglis, 2010;Eva-Maj, Hans, Per-Anders, & Mikael, 2013). The results of our study are consistent in showing that disturbances of the sensory system, quantified by increases in sensory thresholds (i.e., declines in afferent signaling of event detection), are related to, and possibly part of, mechanisms influential in generating greater changes in motor patterns.…”
Section: Association Between Motor and Sensory Changessupporting
confidence: 79%
“…electromyography) during exercise is thought to be largely influenced by a central feed-forward neurophysiological mechanism whereby as motor unit recruitment and firing Reproduced from Swart et al [27], with permission frequency increase, the number of efferent copies received by sensory regions within the brain also increases [39,44,45]. This theory is supported by the relationship between perceptions of effort or exertion and the increase in central drive required to exercise at higher intensities and/or during periods of muscle weakening resulting from peripheral fatigue [46] or partial paralysis [47,48]. Indeed, we have recently shown that elevated peripheral fatigue and a concomitant increase in central drive is associated with an increase in RPE during constant-load, high-intensity cycling [46].…”
Section: Neural Regulation Of Perceptionsmentioning
confidence: 96%
“…It was postulated that if force sense arose entirely from a central mechanism (McCloskey 1981), accurate force matching should be achievable at such different lengths. On the other hand, if stretch receptor afferents contributed to force sense (Luu et al 2011), for the same level of motor command at the two lengths, the force perceived at the longer length should be greater. This would be a consequence of the increased afferent activity in the stretched muscle.…”
Section: Discussionmentioning
confidence: 96%
“…Alternatively, the sense of force may not be generated entirely centrally. It has recently been proposed that peripheral signals, including a component from muscle spindles, contribute to the sense of muscle force (Luu et al 2011). Here the authors saw the peripheral contribution, not as a pure exafference, rather as a reafference generated in response to the motor command.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation